Connecting and being connected: investigating friending practices across multiple social networking sites. Issue 3 (11th May 2021) - Yuan, Chien Wen; Lee, Yu-Hao
Abstract : Purpose: Social networking sites (SNSs) offer people the possibility of maintaining larger networks of social ties, which also entails more complex relationship maintenance across multiple platforms. Whom to "friend" and via which platform can involve complex deliberations. This study investigates the relationships between users' perceived friending affordances of five popular SNSs (Facebook, Twitter, Instagram, Snapchat and LinkedIn) and their friending behaviors concerning strong ties, weak ties (existing and latent ties) and parasocial ties. Design/methodology/approach: An online survey using Qualtrics was provided to participants ( N  = 626) through Amazon's Mechanical Turk (MTurk). The survey asked their SNS use and their friending behaviors with different ties on each of the sites. Findings: Users' friending decisions are dependent on an interplay of socio-technical affordances of each SNS and specific needs for the ties. The authors found that the affordances of bridging social capital and enjoyment are aligned with friending weak and parasocial ties, respectively. The affordances of bonding social capital were not valued to friend strong ties. Originality/value: The study extends the affordance and social capital literature by assessing users' perceived, contextualized SNS affordances in relation to actual communication behaviors in friending different social ties. This approach provides contextualized insights to friending decisions and practices on SNSs.